Reducing length of stay in patients following liver transplantation using the model for continuous improvement. Issue 1 (13th March 2023) - Sachar, Yashasavi; Alamr, Abdulrhman; Gob, Alan; Tang, Ephraim; Teriaky, Anouar; Qumosani, Karim; Weernink, Corinne; Dodds, Melanie; Thomas, Kelly; Sinclair, Lynne; Skaro, Anton; Brahmania, Mayur
Abstract : Length of stay (LOS) is a significant contributor to overall patient outcomes for patients undergoing liver transplantation. This study documents a quality improvement project aiming to reduce the median post-transplant LOS for liver transplant patients. We instituted five Plan–Do–Study–Act cycles with the goal of reducing LOS by 3 days from a baseline median of 18.4 days over 1 year. Balancing measures such as readmission rates ensured any decrease in stay was not associated with significantly increased patient complications. Over the 28-month intervention period and 24-month follow-up period, there were 193 patients discharged from hospital with a median LOS of 9 days. The changes appreciated during quality improvement interventions carried over to sustained improvements, with no significant variability in LOS postintervention. Discharge within 10 days increased from 18.4% to 60% over the study period, with intensive care unit stay decreasing from a median of 3.4–1.9 days. Thus, the development of a multidisciplinary care pathway, with patient engagement, led to improved and sustained discharge rates with no significant differences in readmission rates.